Gambaran Pembelajaran Berbasis Developmentally Appropriate Practice (DAP) di SMK Negeri 1 Semarang: Overview of Developmentally Appropriate Practice (DAP) Based Learning at SMK Negeri 1 Semarang - Andhika Kamal Ridlo; Asep Ardiyanto (JSH: Journal of Sport and Health, 2024)
Students are people who try to develop themselves through the educational process. In the future, they will be the nation's next generation who will run the government as leaders. So the main focus of teaching in the classroom should be to help students develop and learn according to their development. The aim of this research is to provide an overview of Developmentally Appropriate Practices (DAP) based learning at SMK Negeri 1 Semarang. To describe the learning, 2 indicators are used, namely the teacher's beliefs about students and learning practices in the classroom. The research method uses a case study that focuses on class X Vocational School with the class teacher as the subject. The instruments used were questionnaires, interview guides, checklist sheets and observation sheets related to DAP-based classroom activities. The results found a compatibility between teachers' beliefs about students and the DAP principles, namely commonality, individuality, context. However, in practice, teachers are not yet optimal in implementing DAP in the learning process. Suggestions for teachers are that efforts are needed to improve professional competence so that knowledge about the characteristics of child development, teaching approaches or methods that are appropriate to the context, etc. Suggestions for schools to provide adequate facilities for both teachers and students, provide guidance for and also activate their role as supervisors in schools.